The Influence of Sustainability Report Disclosure on the Profitability of Food and Beverage Companies in Indonesia - Ghina Kemala Dewi (Journal Of Business, Finance, and Economics (JBFE), 2024)
Currently, companies are not only preparing financial statements but also need to create sustainability reports. This is important as an indicator of how well the company can manage the impact of its operations on the 3Ps (Profit, People, Planet). This scientific writing aims to analyze the effect of sustainability report disclosure on the profitability of companies, proxied by Return on Assets (ROA) and Return on Equity (ROE), in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period of 2021-2022. The analysis method in this research uses quantitative data. The testing stages in this study include validity tests, reliability tests, classical assumption tests, multiple linear regression, partial tests (T-tests), simultaneous tests (F-tests), and the coefficient of determination (R²). The sample used in this study consists of food and beverage companies listed on the IDX, with a total of 17 companies meeting the predetermined criteria. The data used is secondary data, with multiple linear regression analysis tested using SPSS software version 23 as the analytical tool. The results of the t-test on the influence of the sustainability report on Return on Assets show that the economic category has a significance value of 0.197 > 0.05, meaning that the economic category does not partially affect Return on Assets. The environmental category has a significance value of 0.558 > 0.05, meaning that the environmental category does not partially affect Return on Assets. The social category has a significance value of 0.100 > 0.05, meaning that the social category does not partially affect Return on Assets. The results on the influence on Return on Equity indicate that the economic category has a significance value of 0.813 > 0.05, meaning that the economic category does not partially affect Return on Equity. The social category has a significance value of 0.875 > 0.05, meaning that the social category does not partially affect Return on Equity.